2015
DOI: 10.1142/s0218126616500109
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Wide Tuning Range Membership Function Generator and Its Application

Abstract: A versatile low-voltage CMOS circuit with a trapezoidal transconductance characteristic and independently programmable slope, height and horizontal position is designed in 0.18[Formula: see text][Formula: see text]m standard CMOS technology. The proposed circuit is constructed from combination of two linearization methods to enhance the linearity in low voltage applications. A [Formula: see text]118[Formula: see text]dB THD was obtained for a 400[Formula: see text]mV peak to peak differential input voltage at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…31 Many programmable MFGs have been reported in the literature. [13][14][15][16][17][18][19] Most of these works have utilized current or transconductance modes to improve design functionality. Kachare et al 13 demonstrated a triangular/trapezoidal MFG in 0.5 μm CMOS technology.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…31 Many programmable MFGs have been reported in the literature. [13][14][15][16][17][18][19] Most of these works have utilized current or transconductance modes to improve design functionality. Kachare et al 13 demonstrated a triangular/trapezoidal MFG in 0.5 μm CMOS technology.…”
Section: Related Workmentioning
confidence: 99%
“…11,12 Various MFGs have been proposed in the literature based on the conventional complementary metal-oxide-semiconductor (CMOS) technology. [13][14][15][16][17][18][19] However, most of them are not capable of working properly in deep nanoscale commercial technologies. Moreover, they cannot fully control the shape of the generated output.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations